Preparation method of environment-friendly self-emulsifying epoxy vinyl carbon fiber sizing agent
By preparing an environmentally friendly self-emulsified epoxy vinyl carbon fiber sizing agent with epoxy groups and carbon-carbon double bonds, the problem of poor connection between carbon fiber and different types of resins is solved, and the mechanical properties and stability of the composite material are significantly improved.
Patent Information
- Application Number
- CN202411386437.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
It is difficult to find a carbon fiber sizing agent that can be adapted to epoxy resin and vinyl resin at the same time, resulting in poor connection between carbon fiber and different types of matrix resins, affecting the mechanical properties of the composite material.
A method for preparing an environmentally friendly self-emulsified epoxy vinyl carbon fiber sizing agent is adopted, and the preparation of polyetheramines, isocyanate trimers, epoxy resins, acrylate compounds containing carbon-carbon double bonds and allyl polyether compounds are carried out. Graft polymerization reaction forms a polymer polymer with an epoxy group and a carbon-carbon double bond, and obtains a water-soluble sizing agent suitable for the two resins by emulsification by deionized water.
The reinforced connection between carbon fiber and epoxy resin and vinyl resin is achieved, the mechanical properties of the composite material are improved, and the average particle size of the sizing agent is small and the stability is good, which is suitable for the application of a variety of resins.
Smart Images

Figure CN119241796A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber material synthesis, and in particular to a method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent. Background Art
[0002] Carbon fiber is widely used in aerospace, rail transportation, shipbuilding, automobile, wind power generation, sports goods and other fields due to its light weight, high strength, corrosion resistance and good chemical stability. However, the compatibility of unslurried carbon fiber with matrix resin is poor, which cannot improve the application performance of carbon fiber reinforced composite materials. Sizing is an important means of carbon fiber modification and reinforcement composite materials. After sizing, the sizing agent not only serves as a protective layer to better protect the carbon fiber and reduce the fuzzing and broken wires of the carbon fiber, but also as the interface connection layer between the fiber and the matrix resin, it can better infiltrate and bond with the matrix resin, thereby improving the comprehensive mechanical properties of carbon fiber composite materials.
[0003] The commonly used resin matrices in carbon fiber composites are mainly epoxy resin, vinyl resin, etc. Epoxy resin has excellent heat resistance and stability and is a commonly used matrix resin for carbon fiber reinforced composites; vinyl resin is a thermosetting resin prepared by unsaturated carboxylic acid and epoxy resin in styrene. Vinyl resin not only has the outstanding mechanical properties of epoxy resin, but also has the good mechanical processing properties of unsaturated polyester resin. It also has excellent chemical stability and good water resistance. It is one of the resins with broad application prospects.
[0004] Therefore, carbon fiber needs to be combined with different types of resins to prepare composite materials. According to the principle of like dissolves like, different resin matrices need to choose corresponding sizing agents. However, in order to ensure that carbon fiber can have a good connection with epoxy resin or vinyl resin, there is no sizing agent that can meet the applicability of different types of matrix resins at the same time.
[0005] In view of this, the present invention prepares a carbon fiber sizing agent which is compatible with both epoxy resin and vinyl resin. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a carbon fiber sizing agent which is compatible with both epoxy resin and vinyl resin, so as to obtain an environmentally friendly water-soluble polymer solution with a small average particle size and good dilution stability.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows: a method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent, comprising the following steps:
[0008] S1. Place a four-necked flask in an oil bath, add polyetheramine and isocyanate trimer into the flask, heat, and react for 1-2 hours;
[0009] S2, adding epoxy resin, heating up to carry out graft polymerization reaction, the reaction time is 1-2h;
[0010] S3, adding an acrylic acid ester compound containing a carbon-carbon double bond or an allyl compound containing an amino hydroxyl group, and continuing to raise the temperature to carry out a graft polymerization reaction, the reaction time is 1-2.5 hours;
[0011] S4, adding an allyl polyether compound to carry out a grafting chain extension reaction, the reaction time is 1-2 hours;
[0012] S5, adding the end-capping compound polyoxyethylene ether to carry out the end-capping termination polymerization reaction, the reaction time is 1-2h; after the reaction is completed, the temperature is lowered to room temperature to obtain a viscous high molecular polymer;
[0013] S6. Preheat the deionized water in a 60°C water bath for 1 hour, then slowly drop the deionized water into a high-speed disperser containing the polymer in step S5 for phase transition emulsification, then cool to room temperature, cool and filter the material to obtain an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent.
[0014] Furthermore, the heating temperature in step S1 is 40-50°C; the temperature in step S2 is 60-70°C; and the temperature in step S3 is 80-95°C.
[0015] Furthermore, the polyetheramine compound in step S1 includes one or more of D230, D400, D1000, D2000, and T5000.
[0016] Furthermore, the isocyanate trimer in step S1 includes one or more of HDI trimer, MDI trimer, HMDI trimer, and IPDI trimer.
[0017] Furthermore, the epoxy resin in step S2 includes one or more of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, and bisphenol F epoxy resin.
[0018] Furthermore, the acrylic acid ester compound containing a carbon-carbon double bond in step S3 includes one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.
[0019] Furthermore, the allyl compound containing amino hydroxyl group in step S3 includes one or more of acrylamide, 4-amino-2-butene-1-ol, and 1-amino-3-butene-2-ol.
[0020] Furthermore, the molecular weight of the allyl polyether in the allyl polyether in step S4 includes one or more of 700, 800, 900, 1000, and 2000.
[0021] Furthermore, the polyoxyethylene ether compound in step S5 includes one or more of fatty alcohol polyoxyethylene ether, pesticide emulsifier, and fatty amine polyoxyethylene ether, wherein fatty alcohol polyoxyethylene ether includes MOA-3, MOA-4, MOA-5, etc.; pesticide emulsifiers include 600#, 600-1#, 400#, 403#, etc.; fatty amine polyoxyethylene ether includes AC-1801, AC-1802, AC-1810, etc.
[0022] Furthermore, the raw materials for phase transition emulsification in step S6 are composed of the following raw materials by weight, including 30-60 parts of high molecular polymer and 40-70 parts of deionized water.
[0023] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0024] 1. The carbon fiber sizing agent prepared in the present application is an environmentally friendly water-soluble polymer emulsion, which is conducive to the carbon fiber sizing process operation; the molecular structure of the sizing agent contains epoxy groups, amino groups and a large number of carbon-carbon double bonds. The epoxy groups and amino groups in the sizing agent are compounded with epoxy resins to participate in the curing reaction of epoxy resins to form stronger connections, thereby improving the interfacial interaction force of carbon fiber reinforced epoxy resins.
[0025] 2. In addition, the unsaturated carbon-carbon double bonds in the molecular structure of the sizing agent can participate in the curing reaction of the vinyl resin, significantly improve the interfacial force between the carbon fiber and the vinyl resin, and achieve a strong chemical connection in the interface layer, which is beneficial to improving the comprehensive mechanical properties of the carbon fiber reinforced vinyl composite material.
[0026] 3. The carbon fiber sizing agent prepared in the present application has a small average particle size, good stability and film-forming properties, and can be compatible with both epoxy resin and vinyl resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart of a method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent in a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0029] Reference Figure 1As shown, a preferred embodiment of the present invention is a method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent, comprising the following steps:
[0030] S1. Place a four-necked flask in an oil bath, add polyetheramine and isocyanate trimer into the flask, heat to 40-50°C, and react for 1-2h;
[0031] Among them, polyetheramine compounds include but are not limited to D230, D400, D1000, D2000, T5000; isocyanate trimers include but are not limited to HDI trimer, MDI trimer, HMDI trimer, IPDI trimer;
[0032] S2, adding epoxy resin, heating to 60-70°C for graft polymerization reaction, the reaction time is 1-2h;
[0033] Among them, epoxy resins include but are not limited to bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin,
[0034] S3. Add an acrylate compound containing a carbon-carbon double bond or an allyl compound containing an amino hydroxyl group, and continue to raise the temperature to 80-95°C for graft polymerization reaction. The reaction time is 1-2.5 hours; wherein the acrylate compound containing a carbon-carbon double bond includes but is not limited to hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.
[0035] Allyl compounds containing amino hydroxyl groups include, but are not limited to, ammonia hydroxymethyl acrylamide, 4-amino-2-butene-1-ol, and 1-amino-3-butene-2-ol;
[0036] S4, adding an allyl polyether compound to carry out a grafting chain extension reaction, the reaction time is 1-2 hours;
[0037] Wherein, the molecular weight of the allyl polyether in the allyl polyether includes but is not limited to 700, 800, 900, 1000, 2000;
[0038] S5, adding the end-capping compound polyoxyethylene ether to carry out the end-capping termination polymerization reaction, the reaction time is 1-2h; after the reaction is completed, the temperature is lowered to room temperature to obtain a viscous high molecular polymer;
[0039] Among them, polyoxyethylene ether compounds include but are not limited to fatty alcohol polyoxyethylene ether, pesticide emulsifiers, fatty amine polyoxyethylene ethers; fatty alcohol polyoxyethylene ethers include MOA-3, MOA-4, MOA-5, etc.; pesticide emulsifiers include 600#, 600-1#, 400#, 403#, etc.; fatty amine polyoxyethylene ethers include AC-1801, AC-1802, AC-1810, etc.;
[0040] S6. Preheat the deionized water in a 60°C water bath for 1 hour, then slowly drop the deionized water into a high-speed disperser containing the polymer in step S5 for phase transition emulsification, then cool to room temperature, cool and filter the material to obtain an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent.
[0041] The following is an explanation with reference to specific embodiments.
[0042] Example 1
[0043] A method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent comprises the following steps:
[0044] Step 1: Dehydrate polyetheramine D1000 before use, weigh 1 mol of polyetheramine 1000 and place it in a 4-necked flask, place the flask in an oil bath, heat the oil bath to 50°C, build a reaction device with a stirrer, a serpentine condenser, and a thermometer, stir the polyetheramine D1000 at a speed of 180-200 rpm; wait for the temperature of the reaction system to stabilize;
[0045] Step 2: Add 2 mol IPDI trimer, rotation speed 200-220 rpm, reaction time 2 hours;
[0046] Step 3: Add 1 mol of epoxy resin E55, rotate at 200-220 rpm, raise the reaction temperature to 70°C, and further react with isocyanate for 2 hours;
[0047] Step 4: Add 1 mol of 4-amino-2-butene-1-ol, rotate at 200-220 rpm, and react at 85°C for 2 hours with isocyanate;
[0048] Step 5: Then add 1 mol of allyl polyethylene glycol APEG700, rotate at 200-220 rpm, and react at 85°C for 2 hours;
[0049] Step 6: Then add 1 mol of aliphatic alcohol polyoxyethylene ether MOA, the speed is 200-220 rpm, the reaction temperature is 85°C, and the reaction is continued for 2 hours;
[0050] Step 7: After the reaction is completed, the temperature is lowered and cooled to room temperature to obtain a viscous high molecular polymer A.
[0051] Step 8: Weigh 0.5kg of polymer A and place it in the pull cylinder;
[0052] Step 9: Weigh 0.5 kg of deionized water into a glass bottle and preheat the deionized water in a 60°C water bath for 1 hour;
[0053] Step 10: First, stir the material in step 8 in a high-speed disperser (speed of about 3000 rpm), slowly drop the warm water prepared in step 9 into the high-speed dispersed material, perform phase transition emulsification for 2 hours, then cool to room temperature, cool and filter the material, and obtain a milky white carbon fiber sizing agent A-01;
[0054] Step 11: Test the solid content, viscosity, pH value, particle size and dilution stability of the sizing agent.
[0055] Performance test: The sizing agent prepared in Example 1 has a solid content of 49.55%, a viscosity of 1005.0 cP (3#, 30 rpm), a pH value of 7.15, and an average particle size of 420 nm. The sizing agent is easily diluted by adding deionized water. The sizing solution with a solid content of 0.5% has good dilution stability. There is no stratification after storage at room temperature for 72 hours, and no precipitation is precipitated at the bottom.
[0056] Application performance evaluation: The sizing agent prepared in Example 1 was used to sizing the unsized carbon fiber filaments, and then the epoxy carbon fiber unidirectional composite sample and the vinyl carbon fiber unidirectional composite sample were prepared by dipping, and the mechanical properties data of the carbon fiber composite sample were tested. The interlayer shear strength of the epoxy carbon fiber composite sample was 82MPa, and the interlayer shear strength of the vinyl carbon fiber composite sample was 85MPa.
[0057] Example 2
[0058] A method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent comprises the following steps:
[0059] Step 1: Dehydrate the polyetheramine D2000 before use, weigh 0.25 mol of the polyetheramine D2000 and place it in a 4-necked flask, place the flask in an oil bath, heat the oil bath to 50°C, build a reaction device with a stirrer, a serpentine condenser, and a thermometer, stir the polyetheramine D2000 at a speed of 180-200 rpm, and wait for the temperature of the reaction system to stabilize;
[0060] Step 2: Add 1.5 mol MDI trimer, rotation speed 200-220 rpm, reaction time 2 hours;
[0061] Step 3: Add 2 mol of epoxy resin E55, rotate at 200-220 rpm, raise the reaction temperature to 85°C, and further react with isocyanate monomer for 2 hours;
[0062] Step 4: Add 1 mol of 4-amino-2-butene-1-ol, rotate at 200-220 rpm, and react at 85°C for 2 hours with isocyanate;
[0063] Step 5: Then add 0.5 mol of allyl polyethylene glycol APEG700, rotate at 200-220 rpm, and react at 85°C for 2 hours;
[0064] Step 6: Then add 0.5 mol of aliphatic alcohol polyoxyethylene ether MOA, the speed is 200-220 rpm, the reaction temperature is 85°C, and the reaction is continued for 2 hours;
[0065] Step 7: After the reaction is completed, the temperature is lowered and cooled to room temperature to obtain a viscous high molecular polymer B.
[0066] Step 8: Weigh 0.5kg of polymer B and place it in the pull cylinder;
[0067] Step 9: Weigh 0.5 kg of deionized water into a glass bottle and preheat the deionized water in a 60°C water bath for 1 hour;
[0068] Step 10: First, stir the material in step 8 in a high-speed disperser (speed of about 2000-3000 rpm), slowly drop the warm water prepared in step 9 into the high-speed dispersed material, perform phase transition emulsification for 1.5 hours, then cool to room temperature, cool and filter the material, and obtain a milky white carbon fiber sizing agent B-01;
[0069] Step 11: Test the solid content, viscosity, pH value, particle size and dilution stability of the sizing agent.
[0070] Performance test: The sizing agent prepared in Example 2 has a solid content of 49.00%, a viscosity of 2875.0 cP (4#, 60 rpm), a pH value of 7.01, and an average particle size of 540 nm. The sizing agent is easily diluted by adding deionized water. The sizing solution with a solid content of 0.5% has good dilution stability. There is no stratification after storage at room temperature for 72 hours, and no precipitation is precipitated at the bottom.
[0071] Application performance evaluation: The sizing agent prepared in Example 2 was used to size the unsized carbon fiber filaments, and then the epoxy carbon fiber unidirectional composite sample and the vinyl carbon fiber unidirectional composite sample were prepared by dipping, and the mechanical properties data of the carbon fiber composite sample were tested. The interlayer shear strength of the epoxy carbon fiber composite sample was 89MPa, and the interlayer shear strength of the vinyl carbon fiber composite sample was 80MPa.
[0072] Example 3
[0073] A method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent comprises the following steps:
[0074] Step 1: Dehydrate the polyetheramine D2000 before use, weigh 1 mol of the polyetheramine D2000 and place it in a 4-necked flask, place the flask in an oil bath, heat the oil bath to 50°C, build a reaction device with a stirrer, a serpentine condenser, and a thermometer, stir the polyetheramine D2000 at a speed of 180-200 rpm, and wait for the temperature of the reaction system to stabilize;
[0075] Step 2: Add 2 mol of MDI trimer, rotation speed 200-220 rpm, reaction time 2 hours;
[0076] Step 3: Add 0.5 mol of epoxy resin E44, rotate at 200-220 rpm, raise the reaction temperature to 85°C, and further react with isocyanate monomer for 2 hours;
[0077] Step 4: Add 1 mol of N-hydroxymethyl acrylamide, rotate at 200-220 rpm, and react at 80°C for 2 hours with isocyanate;
[0078] Step 5: Then add 1 mol of allyl polyethylene glycol APEG1000, rotate at 200-220 rpm, and continue the reaction for 2 hours;
[0079] Step 6: Then add 0.5 mol fatty amine polyoxyethylene ether AC-1801, rotate at 200-220 rpm, and continue the reaction for 2 hours;
[0080] Step 7: After the reaction is completed, the temperature is lowered and cooled to room temperature to obtain a viscous high molecular polymer C.
[0081] Step 8: Weigh 0.5kg of high molecular polymer C and place it in the pull cylinder;
[0082] Step 9: Weigh 0.5 kg of deionized water into a glass bottle and preheat the deionized water in a 60°C water bath for 1 hour;
[0083] Step 10: First, stir the material in step 8 in a high-speed disperser (speed of about 2000-3000 rpm), slowly drop the warm water prepared in step 9 into the high-speed dispersed material, perform phase transition emulsification for 2.5 hours, then cool to room temperature, cool and filter the material, and obtain a milky white carbon fiber sizing agent C-01;
[0084] Step 11: Test the solid content, viscosity, pH value, particle size and dilution stability of the sizing agent.
[0085] Performance test: The sizing agent prepared in Example 3 has a solid content of 50.00%, a viscosity of 780.0 cP (3#, 30 rpm), a pH value of 7.50, and an average particle size of 400 nm. The sizing agent is easily diluted by adding deionized water. The sizing solution with a solid content of 0.5% has good dilution stability. There is no stratification after storage at room temperature for 72 hours, and no precipitation is precipitated at the bottom.
[0086] Application performance evaluation: The sizing agent prepared in Example 3 was used to sizing the unsized carbon fiber filaments, and then the epoxy carbon fiber unidirectional composite sample and the vinyl carbon fiber unidirectional composite sample were prepared by dipping, and the mechanical properties data of the carbon fiber composite sample were tested. The interlayer shear strength of the epoxy carbon fiber composite sample was 85MPa, and the interlayer shear strength of the vinyl carbon fiber composite sample was 92MPa.
[0087] Example 4
[0088] A method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent comprises the following steps:
[0089] Step 1: Dehydrate the polyetheramine D1000 before use, weigh 0.5 mol of the polyetheramine D1000 and place it in a 4-necked flask, place the flask in an oil bath, heat the oil bath to 50°C, build a reaction device with a stirrer, a serpentine condenser, and a thermometer, stir the polyetheramine D1000 at a speed of 180-200 rpm, and wait for the temperature of the reaction system to stabilize;
[0090] Step 2: Add 2 mol IPDI trimer, rotation speed 200-220 rpm, reaction time 2 hours;
[0091] Step 3: Add 2 mol of epoxy resin E44, rotate at 200-220 rpm, raise the reaction temperature to 80°C, and further react with isocyanate monomer for 2 hours;
[0092] Step 4: Add 1 mol of N-hydroxymethyl acrylamide, rotate at 200-220 rpm, and react at 80°C for 2 hours with isocyanate;
[0093] Step 5: Then add 1.5 mol of allyl polyethylene glycol APEG1000, rotate at 200-220 rpm, and continue the reaction for 2 hours;
[0094] Step 6: Then add 0.5 mol fatty amine polyoxyethylene ether AC-1801, rotate at 200-220 rpm, and continue the reaction for 2 hours;
[0095] Step 7: After the reaction is completed, the temperature is lowered and cooled to room temperature to obtain a viscous high molecular polymer D.
[0096] Step 8: Weigh 0.4kg of high molecular polymer D and place it in the pull cylinder;
[0097] Step 9: Weigh 0.6 kg of deionized water into a glass bottle and preheat the deionized water in a 60°C water bath for 1 hour;
[0098] Step 10: First, stir the material in step 8 in a high-speed disperser (speed of about 2000-3000 rpm), slowly drop the warm water prepared in step 9 into the high-speed dispersed material, perform phase transition emulsification for 2.5 hours, then cool to room temperature, cool and filter the material, and obtain a milky white carbon fiber sizing agent D-01;
[0099] Step 11: Test the solid content, viscosity, pH value, particle size and dilution stability of the sizing agent.
[0100] Performance test: The solid content of the sizing agent prepared in Example 4 is 39.45%, and the viscosity is 900.0 cP (3 # , 30rpm), pH value is 7.35, average particle size is 500nm, the sizing agent is easily diluted by adding deionized water, the sizing solution with 0.5% solid content has good dilution stability, there is no stratification after storage at room temperature for 72 hours, and no precipitation is precipitated at the bottom.
[0101] Application performance evaluation: The sizing agent prepared in Example 4 was used to sizing the unsized carbon fiber filaments, and then the epoxy carbon fiber unidirectional composite sample and the vinyl carbon fiber unidirectional composite sample were prepared by dipping, and the mechanical properties data of the carbon fiber composite sample were tested. The interlayer shear strength of the epoxy carbon fiber composite sample was 88MPa, and the interlayer shear strength of the vinyl carbon fiber composite sample was 90MPa.
[0102] Example 5
[0103] A method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent comprises the following steps:
[0104] Step 1: Dehydrate polyetheramine D1000 before use, weigh 1 mol of polyetheramine D1000 and place it in a 4-necked flask, place the flask in an oil bath, heat the oil bath to 50°C, build a reaction device with a stirrer, a serpentine condenser, and a thermometer, stir polyetheramine 1000 at a speed of 180-200 rpm; wait for the temperature of the reaction system to stabilize;
[0105] Step 2: Add 2 mol IPDI trimer, rotation speed 200-220 rpm, reaction time 2 hours;
[0106] Step 3: Add 1 mol of epoxy resin E31, rotate at 200-220 rpm, raise the reaction temperature to 85°C, and further react with isocyanate monomer for 2 hours;
[0107] Step 4: Add 1.5 mol of hydroxyethyl acrylate, rotate at 200-220 rpm, and react at 80°C for 2 hours with isocyanate;
[0108] Step 5: Then add 0.5 mol of allyl polyethylene glycol APEG2000, rotate at 200-220 rpm, and continue the reaction for 2 hours;
[0109] Step 6: Then add 1 mol of aliphatic alcohol polyoxyethylene ether MOA, rotate at 200-220 rpm, and continue the reaction for 2 hours;
[0110] Step 7: After the reaction is completed, the temperature is lowered and cooled to room temperature to obtain a viscous high molecular polymer E.
[0111] Step 8: Weigh 0.3kg of high molecular polymer E and place it in the pull cylinder;
[0112] Step 9: Weigh 0.7 kg of deionized water into a glass bottle and preheat the deionized water in a 60°C water bath for 1 hour;
[0113] Step 10: First, stir the material in step 8 in a high-speed disperser (speed of about 1000-2000 rpm), slowly drop the warm water prepared in step 9 into the high-speed dispersed material, perform phase transition emulsification for 2.5 hours, then cool to room temperature, cool and filter the material, and obtain a milky white carbon fiber sizing agent E-01;
[0114] Step 11: Test the solid content, viscosity, pH value, particle size and dilution stability of the sizing agent.
[0115] Performance test: The sizing agent prepared in Example 5 has a solid content of 30.01%, a viscosity of 5005.0 cP (4#, 30 rpm), a pH value of 6.81, and an average particle size of 320 nm. The sizing agent is easily diluted by adding deionized water. The sizing solution with a solid content of 0.5% has good dilution stability. There is no stratification after storage at room temperature for 72 hours, and no precipitation is precipitated at the bottom.
[0116] Application performance evaluation: The sizing agent prepared in Example 5 was used to sizing the unsized carbon fiber filaments, and then the epoxy carbon fiber unidirectional composite sample and the vinyl carbon fiber unidirectional composite sample were prepared by dipping, and the mechanical properties data of the carbon fiber composite sample were tested. The interlayer shear strength of the epoxy carbon fiber composite sample was 80MPa, and the interlayer shear strength of the vinyl carbon fiber composite sample was 84MPa.
[0117] The carbon fiber sizing agent prepared by the invention is an environmentally friendly water-soluble polymer emulsion, which is beneficial to the carbon fiber sizing process operation; and the sizing agent molecular structure contains a large number of epoxy groups, amino groups and unsaturated carbon-carbon double bonds, and these groups can respectively participate in the curing reaction of epoxy resin and vinyl resin, and can significantly improve the interfacial interaction force between carbon fiber and epoxy resin, vinyl resin, and realize the strong chemical connection of the interface layer, which is beneficial to improve the comprehensive mechanical properties of carbon fiber reinforced epoxy resin and vinyl resin composite materials.
[0118] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.
[0119] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A method for preparing an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent, characterized in that: The following steps are involved: S1. Place a four-necked flask in an oil bath, add polyetheramine and isocyanate trimer into the flask, heat, and react for 1-2 hours; S2, adding epoxy resin, heating up to carry out graft polymerization reaction, the reaction time is 1-2h; S3, adding an acrylic acid ester compound containing a carbon-carbon double bond or an allyl compound containing an amino hydroxyl group, and continuing to raise the temperature to carry out a graft polymerization reaction, the reaction time is 1-2.5 hours; S4, adding an allyl polyether compound to carry out a grafting chain extension reaction, the reaction time is 1-2 hours; S5, adding the end-capping compound polyoxyethylene ether to carry out the end-capping termination polymerization reaction, the reaction time is 1-2h; after the reaction, cooling to room temperature to obtain a viscous high molecular polymer; S6. Preheat the deionized water in a 60°C water bath for 1 hour, then slowly drop the deionized water into a high-speed disperser containing the polymer in step S5 for phase transition emulsification, then cool to room temperature, cool and filter the material to obtain an environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent.
2. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The heating temperature in step S1 is 40-50°C; the temperature in step S2 is 60-70°C; the temperature in step S3 is 80-95°C.
3. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The polyetheramine compound in step S1 includes one or more of D230, D400, D1000, D2000, and T5000.
4. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The isocyanate trimer in step S1 includes one or more of HDI trimer, MDI trimer, HMDI trimer and IPDI trimer.
5. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The epoxy resin in step S2 includes one or more of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, and bisphenol F epoxy resin.
6. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The acrylic acid ester compound containing a carbon-carbon double bond in step S3 includes one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.
7. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The allyl compound containing amino hydroxyl group in step S3 includes one or more of acrylamide, 4-amino-2-butene-1-ol, and 1-amino-3-butene-2-ol.
8. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The molecular weight of the allyl polyether in the allyl polyether in step S4 includes one or more of 700, 800, 900, 1000, and 2000.
9. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The polyoxyethylene ether compound in step S5 includes one or more of fatty alcohol polyoxyethylene ether, pesticide emulsifier, and fatty amine polyoxyethylene ether.
10. The method for preparing the environmentally friendly self-emulsifying epoxy vinyl carbon fiber sizing agent according to claim 1, characterized in that: The raw materials for phase transition emulsification in step S6 are composed of the following raw materials by weight, including 30-60 parts of high molecular polymer and 40-70 parts of deionized water.
Citation Information
Cited By
Self-emulsifying high-wear-resistance vinyl carbon fiber sizing agent composition as well as preparation method and application thereof
CN121161604A
